AT THE BEGINNING OF THE 21ST CENTURY, "THE LEGEND OF LAZGI" WAS PERFORMED ON THE STAGE OF THE KHOREZM REGIONAL PUPPET THEATER - Oybek Qulmurodov; Boltaboy Shodiev (Modern American Journals, 2025)
This article discusses the interpretation of the ancient Lazgi melody on the stage of the puppet theater through puppets, highlighting the harmony of music with events and events in the puppet theater, as well as the professional performance of the director and actors.given.
Keywords: Theater, art, Lazgi, shadir jamol, shadir hayol, performance, puppet theater.